Emerging possibilities in the advancement of herbicides to combat acetyl-CoA carboxylase inhibitor resistance - Rajak, Bikash Kumar; Rani, Priyanka; Mandal, Pranabesh; Chhokar, Rajender Singh; Singh, Nitesh; Singh, Durg Vijay (Frontiers in Agronomy, 2023)
Acetyl-CoA carboxylase (ACCase: EC 6.4.1.2) is one of the essential biotins containing enzymes required by plants for fatty acid synthesis and elongation. The unique enzyme is present in its homomeric form in all the Gramineae family, making it a suitable target for developing herbicides selectively against weeds of the Gramineae family. One such example infestation of Phalaris minor in winter wheat crop fields, where aryloxyphenoxypropionates (FOP); cyclohexanediones (DIM) and phenyl pyrazoline (DEN) group of ACCase inhibiting herbicides are used. However, the increasing number of ACCase herbicide resistant weed varieties has compelled agro-scientists to seek varied possibilities for weed control, through Integrated Weed Management (IWM) strategies. Developing new potential herbicides to regain sensitivity in weeds could be an approach to weed control. The current advancement in computational techniques could be of aid in developing new herbicide-like molecules by exploring the genomics, proteomics and structural details of catalytic sites of herbicide action in crops as well as weeds.